Mapping of Research Trends on Didactic Games in Chemistry Learning - Ifan Sa'ban Fauzi; Neneng Windayani; Yulia Sukmawardani (Journal of Educational Sciences, 2026)
The integration of didactic games in chemistry learning has gained increasing scholarly attention as an innovative pedagogical approach to enhance student engagement and conceptual understanding. Despite its growing relevance, systematic mapping of research trends in this area remains limited. This study aims to analyze the development and thematic structure of scientific publications on didactic games in chemistry education through a bibliometric approach. Data were extracted from the Google scholar database and visualized using VOSviewer to generate network, overlay, and density maps of keywords. The analysis reveals that the core terms such as “game,” “chemistry,” and “student” dominate the research landscape, highlighting their role as conceptual anchors. More recent trends indicate a shift toward “gamification,” “learner,” and broader didactic strategies, signaling the expansion of focus beyond classroom implementation. Furthermore, density visualization shows strong clustering around chemistry content and didactic tools, with opportunities for further exploration in personalized learning and the application of games in complex chemical concepts. In conclusion, this study provides a comprehensive overview of the intellectual structure and emerging directions in didactic games research within chemistry learning, offering insights for both theoretical development and practical innovation.